Physiological Cues Involved in the Regulation of Adhesion Mechanisms in Hematopoietic Stem Cell Fate Decision - Kulkarni, Rohan; Kale, Vaijayanti (Frontiers in Cell and Developmental Biology, 2020)
Hematopoietic stem cells (HSC) could have several fates in the body; viz. self-renewal, differentiation, migration, quiescence, and apoptosis. These fate decisions play a crucial role in maintaining homeostasis and critically depend on the interaction of the HSCs with their micro-environmental constituents. However, the physiological cues promoting these interactions in vivo have not been identified to a great extent. Intense research using various in vitro and in vivo models is going on in various laboratories to understand the mechanisms involved in these interactions, as understanding of these mechanistic would greatly help in improving clinical transplantations. However, though these elegant studies have identified the molecular interactions involved in the process, harnessing these interactions to the recipients’ benefit would ultimately depend on manipulation of environmental cues initiating them in vivo: hence, these need to be identified at the earliest. HSCs reside in the bone marrow, which is a very complex tissue comprising of various types of stromal cells along with their secreted cytokines, extra-cellular matrix (ECM) molecules and extra-cellular vesicles (EVs). These components control the HSC fate decision through direct cell–cell interactions – mediated via various types of adhesion molecules –, cell-ECM interactions – mediated mostly via integrins –, or through soluble mediators like cytokines and EVs. This could be a very dynamic process involving multiple transient interactions acting concurrently or sequentially, and the adhesion molecules involved in various fate determining situations could be different. If the switch mechanisms governing these dynamic states in vivo are identified, they could be harnessed for the development of novel therapeutics. Here, in addition to reviewing the adhesion molecules involved in the regulation of HSCs, we also touch upon recent advances in our understanding of the physiological cues known to initiate specific adhesive interactions of HSCs with the marrow stromal cells or ECM molecules and EVs secreted by them.